In vivo evaluation of pharmacological properties of Argentine stingless bee geopropolis - Brodkiewicz, Ivana Yanina (2020)
Propolis is a natural product that has been widely utilized as medicine and dietary supplement because of its broad biological activities. However, although meliponide hive products have many advantages, meliponiculture has not yet become popular in Argentina, and few scientific studies on its chemical composition and/or its bioactive properties were reported, so the use of stingless bee propolis Argentine in popular medicine continues to be based on empirical knowledge. Our work aims to evaluate in vivo anti-inflammatory, antitussive and expectorant activities, and acute toxicity of the Argentine geopropolis ethanol extracts of two stingless bee’s species, Scaptotrigona jujuyensis Schrottky and Tetragonisca fiebrigi Schwarz. Wistar male rats were used for all in vivo studies. Anti-inflammatory activities were evaluated through carrageenan-induced edema and cotton pellet-induced granuloma formation. Antitussive activity was assessed against ammonia-induced cough. Expectorant activity was measured by volume of phenol red in the rats’ tracheas. The extract doses tested were 125, 250, 500, and 1000 mg/kg (p.o.). The safety was evaluated with test of acute toxicity (48 h). Results: The results showed that S. jujuyensis and T. fiebrigi propolis (1000 mg/kg) significantly reduced the carrageenan-induced edema and cotton pellet-induced granuloma formation 3 h post-dosing. In the ammonia liquor-induced cough, both propolis significantly enhanced the latent period and reduced cough frequency as compared with those of the negative control. However, they did not increase the expulsion of red phenol in the treated rats. Conclusions: This study shows that ethanol extracts of S. jujuyensis and T. fiebrigi propolis have anti-inflammatory and antitussive effects. These findings would justify the use of geopropolis in medicine as a potential phytotherapeutic product. Graphical abstract: [Figure not available: see fulltext.]